Pulmonary embolectomy: preoperative resuscitation - Ugarte Artola, Raúl (Cirugía del Uruguay, 1971)
The paper refers to a case of Trendelenburg's operation performed as consequence of pulmonary embolism eight days after leg fracture. Even though the embolus was removed and the pulmonary artery was sutured restoring heart-beat, the patient" died shortly afterwards. Preoperatory reviva! therapy should be employed in order to reduce risk.